2017
DOI: 10.1007/s40615-016-0327-8
|View full text |Cite
|
Sign up to set email alerts
|

Sexual Health in a Social and Cultural Context: a Qualitative Study of Young Latina Lesbian, Bisexual, and Queer Women

Abstract: Previous research on sexual minority and Latina women suggests that Latina lesbian, bisexual, and queer (LBQ) women may be at high risk for sexually associated and transmitted infections, but research on the sexual health and practices of this population is limited. This qualitative study explored the knowledge, attitudes, and values related to sexual health among a purposive sample of Latina LBQ women living in Seattle, WA. Latina LBQ women (N = 14) were recruited to participate in in-depth interviews about t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
1
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 42 publications
2
1
0
Order By: Relevance
“…Of note, our study is among the few qualitative studies to include a significant proportion of sexual diverse Latinas. In line with previous research with sexual diverse Latina young adults (Gattamorta & Quidley-Rodriguez, 2018; Santos et al, 2017), sexual diverse Latinas in our study reported stressful gendered expectations shaped by both machismo and marianismo. This highlights how socialization into traditional Latinx cultural values around gender in the family and community involving devotion to child rearing, virginity, and deference functions to maintain and reproduce gender inequality.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Of note, our study is among the few qualitative studies to include a significant proportion of sexual diverse Latinas. In line with previous research with sexual diverse Latina young adults (Gattamorta & Quidley-Rodriguez, 2018; Santos et al, 2017), sexual diverse Latinas in our study reported stressful gendered expectations shaped by both machismo and marianismo. This highlights how socialization into traditional Latinx cultural values around gender in the family and community involving devotion to child rearing, virginity, and deference functions to maintain and reproduce gender inequality.…”
Section: Discussionsupporting
confidence: 92%
“…We have highlighted that SDLs may be treated as titillating sexual objects as a result of how the intersection of their racial/ethnic, sexual, and gender identities are perceived by others. This extends previous studies that have shown that racial discrimination plays a role in the experiences of sexual objectification of sexual diverse Latinas (Chmielewski, 2017; Santos, Williams, Rodriguez, & Ornelas, 2017) and sexual diverse Latinos (Bianchi et al, 2010; Ibañez et al, 2009). The sexual objectification reported by our sample is noteworthy given that studies have found it to be associated with perceived likelihood of sexual and intimate partner violence and physical safety anxiety (Flores et al, 2018).…”
Section: Discussionsupporting
confidence: 88%
“…Black gay and bisexual men consistently account for the largest number of HIV infections each year (CDC, 2015). Though this is a bourgeoning area of research with growing opportunities for national funding to reduce negative sexual health outcomes (e.g., HIV and/or sexually transmitted infections (STIs)), very little attention has been paid to bisexual men in particular, especially bisexual men of color (Crawford, Allison, Zamboni, & Soto, 2002; Malebranche, Arriola, Jenkins, Dauria, & Patel, 2010; Santos, Williams, Rodriguez, & Ornelas, 2017; Zamboni & Crawford, 2007). In fact, research that specifically focuses on health among bisexual men—disaggregated or separate from those who identify as gay, lesbian, or heterosexual— is limited; many samples are small or insufficient, and as a result, bisexual participants are oftentimes collapsed into one ‘sexual minority’ subgroup (Brewster & Moradi, 2010; Dodge, Sandfort, & Firestein, 2007).…”
mentioning
confidence: 99%